2016
DOI: 10.18820/2519593x/pie.v34i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Insights from traditional initiation teachers (Basuwe) on the influence of male traditional initiation (lebollo) on the behaviour of schoolboys

Abstract: This article aims to describe the outcomes of traditional initiation schools (lebollo), identify reasons for initiates' deviant behaviour at school after returning from lebollo and offer some suggestions on how to reduce deviant behaviour that may be linked to lebollo. The literature review has shown that lebollo aims to equip initiates with competencies that are necessary for adulthood. A content analysis of data emanating from interviews with two traditional initiation teachers (basuwe) identify initiates yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The government should play a critical role in this regard by providing training and financial support for initiation school programmes. The immorality and transgression of initiates should also be addressed as they create a misperception about the teachings and practices in initiation schools [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The government should play a critical role in this regard by providing training and financial support for initiation school programmes. The immorality and transgression of initiates should also be addressed as they create a misperception about the teachings and practices in initiation schools [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the AIDS Foundation of South Africa [ 7 ], the owner of an initiation school appoints men to reside with initiates throughout the duration of the initiation. Among these men, some are teachers ( Basuwe ), responsible to impart cultural knowledge, others cook and provide caring to initiates, and senior men act as supervisors of teachers in instances when the owner is absent [ 14 ].…”
Section: Descriptionmentioning
confidence: 99%
“…Opponents of initiation schools (Ntombana 2011:636), however, believe that the behaviour and actions of initiated boys do not conform to the expectations that are carried by the ritual; even though they have undergone the ritual, their lives are the same as when they were boys. Little research has been done on the possible influence of initiation schools on learner behaviour (Mohlaloka et al 2016) and even less on how to address behavioural problems seemingly stemming from initiation schools (Mohlaloka 2014). Mohlaloka et al (2016) found that many formal schoolteachers struggle to deal with the deviant behaviour of boys returning from initiation schools.…”
Section: Discipline and Ill-discipline In Government Schools Stemming From Learner Participation In Initiation Schoolsmentioning
confidence: 99%
“…He maintains that these principles guide African indigenous education. Despite criticism directed against 'lebollo' [circumcision] (Mohlaloka et al 2016;Ntombana 2011), there is an upsurge of young boys attending initiation schools in post-apartheid South Africa. It is argued that this is because of the resurgence of young people's respect for traditional authority (Malisha, Maharaj & Rogan 2008).…”
Section: Possible Solutions To Ill-discipline and Disciplinementioning
confidence: 99%
“…Unruly and antisocial behaviour -such as bullying, gangsterism and suicide -seems to be at the centre of the said ill-discipline plaguing education. Researchers (Mohlaloka, Jacobs & De Wet 2016) argue that:…”
Section: Discipline and Ill-discipline In Government Schools Stemming From Learner Participation In Initiation Schoolsmentioning
confidence: 99%